Penguatan Literasi Digital di Sekolah Dasar melalui Kolaborasi dalam Program PkM-KKN - Arifin Maksum; Arita Marini; Endang M. Kurnianti; Dinda Ayu Putri; Salsabila Rizky; Aulia Fahsa; Annisa Maghfira Pramawita; Chairunnisa Ussabrina; Leola Dewiyani; Desy Safitri (LPPI UMN AL WASHLIYAH, 2025)
The implementation of the PkM KKN program at SDN Pondok Kopi 03 aims to empower elementary school teachers in realizing digitally literate schools through the use of digital games as a means to build literacy collaboratively with Universitas Negeri Jakarta. This approach is designed to enhance the effectiveness of teaching and student engagement by creating a more interactive, enjoyable, and meaningful learning environment, while also promoting the development of 21st-century skills such as critical thinking, problem-solving, and collaboration. The main objective of this activity is to strengthen teachers' pedagogical capacity, digital literacy, and creativity through an understanding of educational game design principles, selecting curriculum-relevant games, and integrating them into effective teaching strategies. The results of this program demonstrate improvements in teacher competence in creating innovative and adaptive learning environments, which are expected to contribute significantly to the sustainable improvement of the quality of primary education. The collaboration between schools and higher education institutions has fostered a supportive educational ecosystem and strengthened the roles of both parties in developing learning innovations. The application of educational technology through this approach has also fostered greater confidence among teachers in using digital tools in the classroom.